GLUCOSE HOMEOSTASIS AND ΑSSESSMENT OF Β-CELL FUNCTION BY 3-HOUR ORAL GLUCOSE TOLERANCE (OGTT) IN PATIENTS WITH Β-THALASSEMIA MAJOR WITH SERUM FERRITIN BELOW 1,000 NG/DL: RESULTS FROM A SINGLE ICET-A CENTRE: OGTT in thalassemia and iron overload - De Sanctis, Vincenzo; Soliman, Ashraf; Daar, Shahina; Tzoulis , Ploutarchos; Di Maio, Salvatore; Kattamis, Christos (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Aims: The primary aim of this study was to evaluate retrospectively the glucose homeostasis and surrogate indexes of insulin sensitivity and resistance, during a 3-hour oral glucose tolerance test (OGTT), in β- thalassemia major patients (β-TM) with serum ferritin (SF) below 1,000 ng/mL. Patients and methods: The retrospective cohort study evaluated the medical records of 24 β-ΤΜ patients from 2010 to 2022. Αt the year of study the mean age of patients was 31.0 ± 4.1 (20-37.11) years; 13 (54.1%) were females. The most commonly used iron chelator was deferoxamine (DFO: 75%), followed by deferiprone (DFP:12.5%) and deferasirox (DFX: 12.5%). Insulin sensitivity and resistance indexes were derived from OGTT. A liver iron concentration (LIC) < 3 mg/g d.w. and a global heart T2* value < 20 ms were considered as conservative cut-off values for insignificant iron overload (IOL). Results: The mean SF levels in the whole study cohort population at the age of evaluation was 549.6 ± 232.3 ng/mL. Based on the SF levels, two groups were identified: Group A (N = 14) < 500 ng/mL and Group B (N=10) 500-1,000 ng/mL. Normal glucose tolerance (NGT) during OGTT was observed in 4 patients of Group A (28.5 %) and in 5 patients of Group B (50%) (P: 0.29). The remaining 15/24 patients (62.5%) had glucose dysregulation (GD). The mean age at starting iron chelation therapy (ICT) and the mean SF peak in Group A versus Group B were significantly higher in group Α. The GD was associated with significantly attenuated IGI (first phase of insulin response) and impaired oral disposition index (oDI). Hypogonadotropic hypogonadism (HH) was the most common associated endocrine complication in both groups of patients. Conclusions: This study showed that efficient iron chelation monotherapy in patients with β-TM and SF < 1,000 ng/ml did not entirely prevent glucose metabolism disorders, insulin secretion and sensitivity, and development of acquired hypogonadism.